Chaetophractus vellerosus (Cingulata: Dasypodidae) - Carlini, Alfredo Armando (2016)
Chaetophractus vellerosus (Gray, 1865) is commonly called Piche llorón or screaming hairy armadillo. Chaetophractus has 3 living species: C. nationi, C. vellerosus, and C. villosus of Neotropical distribution in the Bolivian, Paraguayan, and Argentinean Chaco and the southeastern portion of Buenos Aires Province. C. vellerosus prefers xeric areas, in high and low latitudes, with sandy soils, but is able to exist in areas that receive more than twice the annual rainfall found in the main part of its distribution. It is common in rangeland pasture and agricultural areas. C. vellerosus is currently listed as "Least Concern" by the International Union for Conservation of Nature and Natural Resources and is hunted for its meat and persecuted as an agricultural pest; however, the supposed damage to agricultural-farming lands could be less than the beneficial effects of its predation on certain species of damaging insects.